2016
DOI: 10.1111/bph.13467
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 shifts the mediator of bradykinin‐induced relaxation from NO to H2O2 in resistance arteries from patients with cardiovascular disease

Abstract: BACKGROUND AND PURPOSEWe tested the hypothesis that in resistance arteries from cardiovascular disease (CVD) patients, effects of an endotheliumdependent vasodilator depend on the contractile stimulus. EXPERIMENTAL APPROACHArteries dissected from parietal pericardium of cardiothoracic surgery patients were studied by myography and imaging techniques. Segments were sub-maximally contracted by K + , the TxA 2 analogue U46619 or endothelin-1 (ET-1). KEY RESULTSRelaxing effects of Na-nitroprusside were comparable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 52 publications
7
44
2
Order By: Relevance
“…and table ). Figure A confirms earlier findings in pericardial resistance arteries from a different group of patients .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…and table ). Figure A confirms earlier findings in pericardial resistance arteries from a different group of patients .…”
Section: Resultssupporting
confidence: 90%
“…Albeit small, the significantly smaller efficacy of H 2 O 2 during contraction stimulated by U46619 compared to ET‐1 persisted in the presence of inhibitors of COX, NOS, K Ca 2.3 and K Ca 3.1 (table ). Figure B confirms earlier findings in pericardial resistance arteries from a different group of patients .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we used an ET-1-induced model of endothelial dysfunction, as studies have demonstrated that ET-1 induces hypertension, with endothelial dysfunction and increased ROS generation (Savoia & Schiffrin, 2006; 2007; Schiffrin, 2007; Wynne et al , 2009; Pollock & Pollock, 2011; Rodrigo et al , 2011; Idris-Khodja et al , 2016; Leurgans et al , 2016). Our data demonstrate that aorta incubated overnight with ET-1 induces increased Phe-mediated contraction and a decrease in ACh-mediated relaxation.…”
Section: Discussionmentioning
confidence: 99%